Surgical management of lateral epicondylitis: a scoping review of published literature - Duncan Muir, MRCS; Helena Blakeway, MBChB; Richard Morris, MRCS; Ali A. Narvani, FRCS; Ahmed Elgebaly, MD; Mohamed A. Imam, FRCS (JSES Reviews, Reports, and Techniques)
Background: Surgical intervention for lateral epicondylitis remains a controversial topic, with its purpose being debated. Recent guidelines have concluded no benefit from surgery when compared to conservative management. Methods: An electronic database search of Ovid Medline via PubMed, EMBASE, and the Web of Science was performed to understand the published literature further. Results: 35 studies incorporating 1564 patients were included. This included 12 trials and 23 observational studies. Most studies reported the benefits of surgery in pain and function despite the majority of studies using a variety of outcome measures. Conclusion: Surgery is reported to treat lateral epicondylitis successfully. However, multicenter studies have yet to be published, and the low number of included patients means that further evidence is required to conclude management.